Substitusi Tepung Daun Kelor (Moringa oleifera L.) dan Tepung Kacang Hijau (Vigna radiate L.) pada Cookies sebagai Alternatif Makanan Tambahan Ibu Menyusui - Puspitadini, Marliyana; Budiono, Irwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Moringa leaf flour (Moringa oleifera L.) and green beans (Vigna radiate L.) have high nutritional content that can be used as ingredients for making cookies as an alternative supplementary food for breastfeeding mothers. The purpose of this study was to analyze the organoleptic and nutritional content of cookies from Moringa leaf flour and green beans. Methods: This type of research was experimental with a completely randomized design (CRD). The independent variables in this study were Moringa leaf flour and mung bean with P1 5%:30%, P2 10%:25%, P3 15%:20%. While the dependent variable is the organoleptic test and the nutritional content of cookies. The subjects of this study were untrained panelists with purposive sampling. The data analysis technique used the one-way ANOVA test with post hoc Bonferroni and if the data distribution was not normal, it used the Kruskal Wallis test. The result of the nutritional content test were carried out by univariate analysis to determine the average difference in cookies. Results: The results of the organoleptic test, the most preferred color parameter was P1 while the most preferred aroma and texture parameters were P2. The results of the P3B nutritional content test showed ash content (2.46%), fat (29.28%), and energy (514.5%). The highest water content was in P2A (5.93%). The highest protein levels were in P3A and P2B (7.78%). The highest carbohydrate content was found in P1A (56.69%). Conclusion: There are differences in organoleptic properties of color and taste and there are differences in proximate levels without fiber to the addition of Moringa leaf flour and green beans.